Ecological Ethics in Islamic Religious Education Textbooks: A Qualitative Representation Analysis - Rahman, Rini; Ismail, Feiby; Nurhayati, Nurhayati; Abu Nazar, Irfan (Pascasarjana Universitas KH. Abdul Chalim, 2025)
Environmental conservation issues have become a central concern in the discourse of Islamic education, particularly in efforts to internalize sustainability values into Islamic Religious Education (IRE) learning in higher education. This article aims to analyze the representation of ecological conservation values in two commonly used IRE textbooks, employing a qualitative analysis approach grounded in Islamic ecotheology. Data were obtained through document analysis of the IRE textbook published by the Ministry of Research, Technology, and Higher Education (Kemenristekdikti) and the textbook authored by Dr. Nurhasanah, as well as through Focus Group Discussions (FGDs) with five IRE lecturers from four universities. The findings indicate that conservation values are more dominantly presented implicitly, with the category of